Effect of Dietary Supplementation of Fenugreek Seed (Trigonella Foenum-Graecum L.) Powder on Body weight, Blood-biochemical Parameters and Immunity in Broilers - Kumar, P.; Kumar, S.; Sihag, S.; Sihag, Z.S. (Indian Journal of Animal Nutrition, 2021)
A six-week study was carried out to investigate the effect of dietary supplementation of Fenugreek seeds (Trigonella foenum-graecum L.) powder (FSP) on serological and immunological parameters in broiler chickens. One hundred and forty four day-old chicks were randomly divided into six dietary treatment groups having 24 birds in each group and three replications of 8 birds each. Supplementation with FSP was done at the rate of 0, 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0% for T1 to T6. The result of the study revealed that there was a significant (p